Evaluation of the surgical approach based on impacted position and direction of mesiodens. Issue 1 (January 2023) - Kimura, Moemi; Yasui, Takazumi; Asoda, Seiji; Nagamine, Hiroki; Soma, Tomoya; Karube, Takeshi; Kodaka, Rie; Muraoka, Wataru; Nakagawa, Taneaki; Onizawa, Katsuhiro
Abstract: Objective: This study aimed to reveal the relationship between the approach of extraction and the position of the mesiodens by systematic classification. Methods: This retrospective study included patients with impacted mesiodens that required computed tomography for extraction. The direction, sagittal and axial position, eruption from the nasal floor, surrounding bone thickness, surgical approach, and anesthesia type for the impacted mesiodens were analyzed. Mesiodens were classified into three groups (V: vertical position, H: horizontal position, and D: direction), and each group was classified into three subgroups (V1, 2, 3; H1, 2, 3; D1, 2, 3). Results: A total of 169 impacted mesiodens were included in this study. The palatal approach was the most common (151 teeth, 89.3%), followed by the labial approach (11 teeth, 6.5%) and nasal floor approach (6 teeth, 3.6%). The bone thickness from the mesiodens to the palatal surface were significantly shorter in palatal far region of nasopalatine duct (H3) than in palatal near region (H2) (P < 0.05). In vertical high position (V3), the percentage of the palatal approach in H3 (87.5%) was higher than that in H2 (71.4%). Additionally, 15 teeth erupting from the nasal floor wherein four were extracted by the nasal floor approach in H2 but only one tooth in H3. Conclusions: Even at higher positions, mesiodens located in the palatal far region tended to be extracted by the palatal approach because of the thin bone thickness.